Formulation of Technology-based Interactive Learning Media to Revitalize Citizens' Political Awareness - Syaifullah; Anggraeni, Leni; Mukarromah; Sandey Tantra Paramitha; Tarekh Febriana Putra; Hendri Irawan (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: As a dynamic educational orientation, efforts to fulfill political awareness require the latest methodological updates. This research offers an ideal media formulation that can help accelerate efforts to revitalize political awareness. Method: To achieve this, the research method applied goes through at least three interrelated stages; 1) qualitative exploration by reviewing research developments in the literature in a study of aligned themes; 2) objective measurement of research subjects (young citizens) using the verbal rating scale (VRS), numeric rating scale (NRS), and graphic rating scale (GRS) methods. The data obtained from these two methods is then used to determine the ideal formulation for realizing political awareness (conceptual framework development, CFD). Results: The measurement results show that the political awareness profile of young citizens is increasingly diverse and shows new trends. The formulation of the best political education media at least fulfills the ideal learning media according to aspects; content, completeness of information, ease of information transactions, and navigation of its use. Novelty: This research offers an innovative framework that can be adapted to evolving socio-political contexts, making it a significant advancement in the field of political education. The positive coordination between awareness (as a learning objective) and the use of technology is a relationship addressed in this study. Concerns that the progressive development of technology might undermine political awareness can be resolved through the analytical findings of this research. Engaging interactive digital tools, such as social media, holds significant potential to be developed as a means of enhancing political awareness.